2008
DOI: 10.2147/cia.s4250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cholinesterase inhibitors on behavioral and psychological symptoms of Alzheimer’s disease: A meta-analysis

Abstract: Objective: To determine the effi cacy of cholinesterase inhibitors (ChEIs) in improving the behavioral and psychological symptoms of dementia (BPSD) in patients with Alzheimer's disease (AD). Data sources: We searched MEDLINE, Cochrane Registry, and the Cumulative Index to Nursing and Allied Health Literature (CINAHL) from 1966 to 2007. We limited our search to English Language, full text, published articles and human studies. Data extraction: We included randomized, double-blind, placebo-controlled trials eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Outcome measures at the 24-week time point were used in the analysis where available. The inclusion criteria allowed for the inclusion of outcomes measured between 3 months and 1 year from baseline (as per the meta-analysis by Campbell et al [ 14 ] in 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome measures at the 24-week time point were used in the analysis where available. The inclusion criteria allowed for the inclusion of outcomes measured between 3 months and 1 year from baseline (as per the meta-analysis by Campbell et al [ 14 ] in 2008).…”
Section: Methodsmentioning
confidence: 99%
“…There is meta-analysis evidence that ChEIs as a class have a statistically significant benefit compared with placebo in treating symptoms of BPSD in patients with AD [ 14 ]. In particular, donepezil (licensed for the symptomatic treatment of mild to moderately severe AD), which contributed the majority of studies to this analysis (6 of 10 studies), was found to have a statistically significant benefit compared with placebo when analysed separately [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a meta-analysis showed that cholinesterase inhibitors had beneficial effects on reducing BPSD with a weighted mean difference of − 1.38 neuropsychiatry inventory point (95% CI − 2.30, − 0.46) with mild to severe AD compared with placebo [35], but most of studies was conducted in AD patients. In this large-scale VaD trial, TZ and donepezil showed modest therapeutic effects for BPSD, with a mean change of − 3.03 for TZ, − 2.21 for donepezil.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis (Campbell et al, 2008) of nine RCTs of AchEi including donepezil, galantamine, and rivastigmine found a significant improvement on neuropsychiatric symptoms with a mean reduction in NPI of −0.1 (standard) and −1.38 (weighted) means.…”
Section: Alzheimer's Diseasementioning
confidence: 99%